Discussion on the Construction of PNT Policies, Regulations and Standard System - Gang LIU; Zuoya ZHENG; Qinghao XUE; Yao WANG (天地一体化信息网络)
The national comprehensive PNT system of systems (SoS) with the BeiDou system as its core is a signifi cant part of the new generation of information infrastructures.Perfect policies, regulations and standards are important prerequisites and guarantees for ensuring its (PNT SoS) orderly development.The development and research progress of PNT policies, regulations and standards system at home and abroad were summarized.The bottleneck and short plate in the development of the PNT SoS were summarized and analyzed.The thinking of the PNT policy, regulation and standard SoS architecture were put forward.Finally, suggestions were given to promote the development of the PNT SoS based on China's national conditions.